Identification Of Novel 14-3-3 Sigma Homodimer Stabiliser In Nasopharyngeal Carcinoma - Jabal, Ghazi Ahmad Al (2023)
14-3-3σ is an acidic homodimer protein with more than one hundred different protein partners associated with oncogenic signalling and cell cycle regulation. Previous studies have shown that 14-3-3σ functions as a potential tumour suppressor and its expression is commonly downregulated in many types of cancer including nasopharyngeal carcinoma (NPC). As the monomers are generally more prone to degradation than dimers, it was hypothesised that a homodimer stabiliser can potentially decrease the degradation of 14-3-3σ. Also, as the 14-3-3σ requires homodimer form to be functionally active, a homodimer stabiliser is expected to also enhance the activity of the 14-3-3σ. However, to date, there is no reported ligand that can bind to the 14-3-3σ dimer interface cavity and stabilise its homodimeric form. Thus, the aim of this study is to identify a potential novel 14-3-3σ homodimer stabiliser. Three different approaches were implemented to identify a potential novel 14-3-3σ homodimer stabiliser, i.e., in silico virtual screening of a commercially available database, searching the literature for compounds reported to target the dimer interface of other 14-3-3 isoforms, and rational design of potentially novel 14-3-3σ homodimer stabilisers. In silico molecular docking and molecular dynamic (MD) simulation with various analysis tools were implemented for the identification of the potential 14-3-3σ homodimer stabiliser